Nutritive evaluation, metabolisable energy and digestible amino acid contents of different indigenous feedstuff for Nile tilapia (Oreochromis niloticus) - Bibi,F. (2021)
Abstract Three trials were executed to examine the nutritive profile, metabolisable energy and digestible amino acid (AA) contents of four indigenous feed ingredients including wheat (W), wheat middling (WM), canola meal (CM) and rapeseed meal (RSM) in Nile tilapia. Three samples of each test ingredient were collected from three different locations of Multan (MUL) and Sukkar (SKR), of Pakistan. The collected three samples were pooled thereafter to make a homogenous/ representative sample of each test ingredient from a particular study site. Nutrients composition, AA and energy digestibility of these indigenous ingredients were evaluated by using laboratory analyses and fish studies. Proximate analysis indicated variations in some of the nutrients due to location (p < 0.05). Differences were also observed in some AA including arginine, lysine, serine, cysteine, glutamic and aspartic acids, histidine, valine and glycine contents of these ingredients (p < 0.05). Digestibility of leucine, glycine and glutamic acid was higher (p < 0.05) in RSM from MUL. Among W samples from MUL, AA digestibility for lysine, threonine, and aspartic acid was higher (p < 0.05). Crude protein, arginine, alanine, serine, and aspartic acid had higher digestibility (p < 0.05), whereas digestibility was lower (p < 0.05) for threonine, valine and tyrosine in RSM from MUL. Metaboliseable energy contents did not differ among W, WM, CM and RSM regarding their origin (p > 0.05). The results indicated that nutritional profiles and their digestibility indices vary with the location for Nile tilapia.